KEARIFAN LOKAL PEMBERDAYAAN MASYARAKAT DALAM PENGELOLAAN DAN PEMBANGUNAN SUMBERDAYA PERIKANAN BERKELANJUTAN DI KOTA BITUNG - Stendy K. Lakoy; Shirley Y.V.I. Goni; Deysi ., Tampongangoy (Sam Ratulangi University, 2021)
This study aims to analyze local wisdom of community empowerment in the management and development of sustainable fisheries resources in Bitung City. This research is a descriptive observational research, with a phenomenological qualitative approach. Respondents in this research were 10 people who were taken by purposive sampling technique with the focus of research using Jim Ife's theory of local wisdom which consists of local knowledge, local values, local skills and local resources. Data was collected by means of observation, interviews and documentation. Data analysis uses steps consisting of data reduction, data presentation and conclusion drawing. The results showed that local wisdom from Bitung City is the charm festival of the Lembeh Strait and Mangrove planting. For the empowerment of local wisdom, indigenous peoples are empowered by conducting training and business capital assistance. Management and empowerment of local communities is carried out by implementing a community-based resource management approach model, thus in developing community-based resource management, namely by creating a self-help community problem solving system and stimulating citizen participation in community affairs in order to achieve the desired goals through the implementation of empowerment, especially in the fisheries sector. sustainable.